A role for DICAM+ mononuclear phagocytes in controlling neuroinflammation in multiple sclerosis - von Essen, Marina Rode; Hansen, Marie Mathilde; El Mahdaoui, Sahla; Hvalkof, Victoria Hyslop; Hansen, Malene Bredahl; Buhelt, Sophie; Sellebjerg, Finn (Frontiers in Immunology, 2025)
Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system (CNS). In MS, CNS-infiltrating monocytes differentiate to tissue resident macrophages which are found in large numbers within the injured areas of the brain where they play a central role in driving disease progression through demyelination and tissue destruction. However, infiltrating monocytes and their derivative macrophages can also serve protective functions. In this study we investigated a possible role of intrathecal mononuclear phagocytes (infiltrating monocytes and macrophages) expressing dual immunoglobulin domain-containing cell adhesion molecule (DICAM) in neuroinflammation. Compared to symptomatic controls (n = 14), treatment-naïve patients with relapsing-remitting MS (n = 21) had a reduced prevalence of DICAM+ mononuclear phagocytes in CSF. When patients were treated with natalizumab (n = 12), an antibody blocking migration of blood leukocytes to the CNS, we observed that DICAM+ monocytes were still recruited to the CSF and that the level of soluble DICAM (sDICAM) in CSF was significantly increased in natalizumab-treated patients (n = 42) compared to untreated patients (n = 43). sDICAM and the prevalence of DICAM+ mononuclear phagocytes in CSF furthermore correlated negatively with concentrations of various cytokines, including TNFα. Analysing the functional properties of DICAM showed that LPS-induced TNFα-production in mononuclear phagocytes was effectively reduced by signalling through surface-bound DICAM. This discovery, together with the observation of a high prevalence of infiltrating DICAM+ mononuclear phagocytes in individuals with no disease or in which disease was kept under control, suggests an immunomodulatory role of DICAM+ mononuclear phagocytes. DICAM has been shown to engage in homophilic interactions with DICAM expressed on the same cell. If sDICAM in a similar way can engage with DICAM on adjacent cells, the increased intrathecal sDICAM of natalizumab-treated patients may help regulate inflammation in a paracrine way. Overall, our data suggest that DICAM+ mononuclear phagocytes play a role in controlling neuroinflammation.